Severe smallness as predictor of adverse perinatal outcome in suspected late small‐for‐gestational‐age fetuses: systematic review and meta‐analysis. (1st September 2022) - Meler, E.; Martinez‐Portilla, R. J.; Caradeux, J.; Mazarico, E.; Gil‐Armas, C.; Boada, D.; Martinez, J.; Carrillo, P.; Camacho, M.; Figueras, F.
ABSTRACT: Objective: To investigate the performance of severe smallness in the prediction of adverse perinatal outcome among fetuses with suspected late‐onset small‐for‐gestational age (SGA). Methods: A systematic search was performed to identify relevant studies in PubMed, Web of Science and Scopus. Late‐onset SGA was defined as estimated fetal weight (EFW) or abdominal circumference (AC) < 10 th percentile diagnosed at or after 32 weeks' gestation, while severe SGA was defined as EFW or AC < 3 rd percentile or < 2 SD. Random‐effects modeling was used to generate hierarchical summary receiver‐operating‐characteristics (HSROC) curves. The performance of severe SGA (as a presumptive diagnosis) in predicting adverse perinatal outcome among singleton pregnancies with suspected late‐onset SGA was expressed as area under the HSROC curve (AUC), sensitivity, specificity and positive/negative likelihood ratios. The association between suspected severe SGA and adverse perinatal outcome was also assessed by random‐effects modeling using the Mantel–Haenszel method and presented as odds ratio (OR). The non‐exposed group was defined as non‐severe SGA (EFW ≥ 3 rd centile). Results: Twelve cohort studies were included in this systematic review and meta‐analysis. The studies included a total of 3639 fetuses with suspected late‐onset SGA, of which 1246 had suspected severe SGA. Significant associations were found between suspected severe SGA and composite adverse perinatal outcome (OR, 1.97 (95% CI, 1.33–2.92)), neonatal intensive care unit admission (OR, 2.87 (95% CI, 1.84–4.47)) and perinatal death (OR, 4.26 (95% CI, 1.07–16.93)). However, summary ROC curves showed limited performance of suspected severe SGA in predicting perinatal outcomes, with AUCs of 60.9%, 66.9%, 53.6%, 57.2%, 54.6% and 64.9% for composite adverse perinatal outcome, neonatal intensive care unit admission, neonatal acidosis, Cesarean section for intrapartum fetal compromise, low Apgar score and perinatal death, respectively. Conclusion: Although suspected severe SGA was associated with a higher risk of perinatal complications, it performed poorly as a standalone parameter in predicting adverse perinatal outcome. © 2022 International Society of Ultrasound in Obstetrics and Gynecology. Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from the abstract to view the translations. RESUMEN: Pequeñez extrema como predictor de resultados perinatales adversos en fetos sospechosos de ser pequeños para la edad gestacional tardía: revisión sistemática y metaanálisis Objetivo: Investigar el rendimiento de la pequeñez extrema en la predicción de resultados perinatales adversos entre los fetos con sospecha de aparición tardía de ser pequeños para la edad gestacional (PEG) . Métodos: Se realizó una búsqueda sistemática para identificar estudios relevantes en PubMed, Web of Science y Scopus. La PEG de aparición tardía se definió como el peso estimado del feto (PEF) o perímetro abdominal (PA) <10 o percentil diagnosticado a las 32 semanas de gestación o posteriormente, mientras que la PEG extrema se definió como el PEF o el PA <3 er percentil o <2 DE. Se utilizó un modelo de efectos aleatorios para generar curvas resumen de las características operativas del receptor jerárquicas (HSROC, por sus siglas en inglés). El valor de la PEG extrema (como diagnóstico provisional) en la predicción del resultado perinatal adverso entre los embarazos con feto único con sospecha de PEG de aparición tardía se expresó por medio del área bajo la curva (ABC) HSROC, la sensibilidad, la especificidad y los cocientes de verosimilitud positivos/negativos. La asociación entre la sospecha de PEG extrema y el resultado perinatal adverso también se evaluó mediante un modelo de efectos aleatorios utilizando el método de Mantel‐Haenszel y se presentó como razón de momios (RM). El grupo no expuesto se definió como PEG no extrema (PEF ≥3 er percentil) . Resultados: En esta revisión sistemática y metaanálisis se incluyeron doce estudios de cohortes. Los estudios incluyeron un total de 3639 fetos con sospecha de PEG de aparición tardía, de los cuales 1246 se tenía sospecha de PEG extrema. Se encontraron asociaciones significativas entre los casos con sospecha de PEG extrema y el resultado perinatal adverso compuesto (RM 1, 97 (IC 95%, 1, 33–2, 92)), el ingreso en la unidad de cuidados intensivos neonatales (RM 2, 87 (IC 95%, 1, 84–4, 47)) y la muerte perinatal (RM 4, 26 (IC 95%, 1, 07–16, 93)). Sin embargo, las curvas ROC resumen mostraron un valor limitado para la sospecha de PEG extrema en la predicción de resultados perinatales, con ABC del 60, 9%, 66, 9%, 53, 6%, 57, 2%, 54, 6% y 64, 9% respectivamente para el resultado perinatal adverso compuesto, el ingreso en la unidad de cuidados intensivos neonatales, la acidosis neonatal, la cesárea por deterioro fetal durante el parto, la baja puntuación de Apgar y la muerte perinatal . Conclusión: Aunque la sospecha de PEG extrema se asoció a un mayor riesgo de complicaciones perinatales, el valor que se le encontró como parámetro independiente para predecir resultados perinatales adversos fue muy poco . 摘要: 严重偏小作为疑似孕晚期小于胎龄儿围产期不良结局的预测因素:系统综述与荟萃分析 目的: 研究严重偏小在预测疑似孕晚期小于胎龄儿(SGA)围产期不良结局方面的表现。 方法: 在PubMed、Web of Science和Scopus等数据库中进行系统检索，以查找有关研究文献。孕晚期SGA的定义是在妊娠32周或更晚的时间诊断确认估测胎儿体重(EFW)或胎儿腹围(AC)低于同孕龄儿的 第10 百分位，严重SGA的定义是EFW或AC小于第3 百分位或小于2 SD。随机效应模型用于生成分层汇总接受者操作特性(HSROC)曲线。严重SGA(作为推定诊断)在预测疑似孕晚期SGA单胎妊娠不良围产结局方面的表现，以HSROC曲线中的面积(AUC)、敏感性、特异性和阳性/阴性似然比表示。疑似严重SGA与不良围产期结局之间的关联亦可通过随机效应模型，采用Mantel‐Haenszel方法进行评估，以优势比(OR)来表示。非暴露组被定义为非严重SGA(EFW ≥ 第 3 百分位)。 结果: T本系统综述与荟萃分析包含12项队列研究。 这些研究覆盖3639名疑似孕晚期SGA胎儿，其中1246名疑似严重SGA。研究发现，疑似严重SGA与复合不良围产期结局(OR，1.97(95%CI，1.33‐2.92))、新生儿重症监护室入院(OR，2.87(95%CI，1.84‐4.47))和围产期死亡(OR，4.26(95%CI，1.07‐16.93))之间存在显著相关性。然而，总结性的ROC曲线则揭示，疑似严重SGA在预测围产期结局方面的表现有限，就复合不良围产期结局、新生儿重症监护室入院、新生儿酸中毒、剖宫产术中胎儿损伤、Apgar评分低和围产期死亡而言，AUC分别为60.9%、66.9%、53.6%、57.2%、54.6%和64.9%。 结论: 尽管疑似严重SGA与较高的围产期并发症风险具有相关性，但它作为独立参数在预测围产期不良结局方面表现不佳。